Analisis Audit Sistem Informasi Kualitas Pelayanan Perbankan Pada Bank HIJ Menggunakan Cobit 5 - Iwid Hidayah Putri; Dieo Alfiky Ananda; Rizky Ramadan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Auditing information systems in the banking sector is a crucial step to ensure optimal service quality. This article discusses how the COBIT 5 framework can be used to assess and improve the quality of banking services. This research utilizes data from HIJ bank, identifies areas that need improvement, and provides recommendations for improving service quality.